PENGARUH PENAMBAHAN PELEPAH KELAPA SAWIT SEBAGAI BAHAN CAMPURAN TERHADAP SIFAT MEKANIK KUAT TEKAN DAN POROSITAS BATU BATA - Teguh Satria Mahlindo; Seno Aji; Sari Anggraini (Institut Teknologi Sawit Indonesia (ITSI), 2019)
This study aimed to determine the effect of oil palm fronds addition as a mixture to the mechanicalproperties of bricks in terms of porosity testing, and compressive strength, and to determine theproper percentage of oil palm frond additions. This research is a type of experiment with arandomized block design (RBD) arranged non-factorial and the data is processed using the SPSS 20Tukey test program. This study used a brick-shaped sample with a length of 19 cm, a width of 9.5 cmand a height of 4.5 cm. Variations in the composition of the added oil palm fronds are 0%, 5%, 10%,15%, and 20%. Parameter mechanical properties of bricks included porosity, and compressivestrength tests. The addition of oil palm fronds with a composition percentage of 0% to 10% affectedthe mechanical properties of the bricks by reducing porosity and increasing the compressive strengthof the bricks. Based on the test results obtained by each of the best test values, namely the minimumporosity value achieved in the percentage of oil palm fronds as much as 10%, which is 18.4%. Theoptimum compressive strength value is achieved on the percentage of oil palm fronds as much as 10%which is equal to 20.5 N / mm²